Direction-specific interaction forces underlying zinc oxide crystal growth by oriented attachment - X. Zhang (Nature Portfolio, 2017)
Crystal growth is a fundamental process, important in a wide range of fields, but the interparticle forces responsible for molecule alignment are not well understood. Here, the authors measure the alignment forces in ZnO using dynamic force spectroscopy, highlighting the role of intervening water molecules.